Analisis faktor-faktor yang mempengaruhi kepuasan konsumen minimarket Alfamidi di Kota Makassar - Mustari Mustari; Ilham Thaief; Muh. Ihsan Said A. (Seminar Nasional LP2M UNM, 2019)
This study aims to analyze and examine the prime service variables consisting of abilities, attitudes, appearance, attention, actions, and responsibilities carried out by Alfamidi minimarket employees that influence customer satisfaction which is part of research that analyzes services based on customer satisfaction. At present the author has conducted research through the planning or design stages until the final stage of the research which is an instrument as a research requirement at the Alfamidi minimarket in Makassar. The research method and approach of this research are tested and analyzed by an operational model of research to increase the number of consumers through excellent service of employees so that it can influence consumer satisfaction at Alfamidi minimarket in Makassar. Excellent service carried out by Alfamidi minimarket employees applied can provide benefits to Alfamidi minimarket companies in Makassar. Based on the research title of the Effect of Excellent Service which includes the ability, attitude, appearance, attention, action, and responsibility influencing the satisfaction of Alfamidi Minimarket Consumers in Makassar, the variables in this study are divided into two variables. Based on the results of the partial test (T test), the results of the study prove that among the six independent variables there are five variables that have a positive effect, namely ability, attitude, appearance, attention, action and one variable that negatively affects responsibility) to the dependent variable. Significantly among the six variables (ability, attitude, appearance, attention, action, and responsibility), there are only two variables that have a significant effect, namely the ability and appearance variables. Simultaneously (F test), the results of the study prove that the independent variables (ability (X1), attitude (X2), appearance (X3), attention (X4), action (X5), and responsibility (X6)) simultaneously have an influence significant impact on consumer satisfaction at Alfamidi Minimarket in Makassar.